L–H transition threshold studies in helium plasmas at JET. (22nd October 2021) - Solano, E.R.; Birkenmeier, G.; Delabie, E.; Silva, C.; Hillesheim, J.C.; Boboc, A.; Carvalho, I.S.; Carvalho, P.; Chernyshova, M.; Craciunescu, T.; de la Luna, E.; Fontdecaba, J.M.; et al.
Abstract: We present a study of the power threshold for L–H transitions ( P LH ) in almost pure helium plasmas, obtained in recent experiments at JET with an ITER-like wall (Be wall and W divertor). The most notable new result is that the density at which P LH is minimum, n ¯ e, min, is considerably higher for helium than for deuterium and hydrogen plasmas. We discuss the possible implications for ITER in its pre-fusion operating power phase.